2013
DOI: 10.1111/jce.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Atrial Fibrillation Termination Sites in the Right Atrium During Complex Fractionated Atrial Electrograms‐Guided Ablation in Patients with Persistent Atrial Fibrillation

Abstract: A half of patients with persistent AF refractory to LA ablation successfully converted to AT or SR during automated CFAE-guided ablation at the RA. The most common critical sites for AF termination were the CT and RA appendage and septum. Patients with AF termination during procedure whether LA CFAE only or after RA CFAE ablation had better outcome with less late recurrence of atrial tachyarrhythmia compared to those without AF termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…Additional CFAE ablation seems to generate unnecessary scarring with worsened rhythm outcomes. Although the extent of CFAE ablation in the current study may be controversial, such as right atrial CFAE, it is not clear whether the antifibrillatory effect of extensive CFAE ablation represents true trigger ablation or a reduction in critical mass. Several new strategies for AF ablation have been introduced, such as rotor, dominant frequency, or driver domain .…”
Section: Discussionmentioning
confidence: 89%
“…Additional CFAE ablation seems to generate unnecessary scarring with worsened rhythm outcomes. Although the extent of CFAE ablation in the current study may be controversial, such as right atrial CFAE, it is not clear whether the antifibrillatory effect of extensive CFAE ablation represents true trigger ablation or a reduction in critical mass. Several new strategies for AF ablation have been introduced, such as rotor, dominant frequency, or driver domain .…”
Section: Discussionmentioning
confidence: 89%
“…18 The number of segments with additional applied ablations was 1 in 81 patients (32.4%), 2 in 21 patients (8.4%), and >3 in 73 patients (29.2%). A total of 146 (60.6%) patients required RA ablation for noninducibility.…”
Section: Acute Ablation Outcomesmentioning
confidence: 99%
“…CFAE in the right atrium as well as LA have been described, and Chen et al reported that half of the patients with persistent AF refractory to LA ablation successfully converted to AT or SR during CFAEguided ablation at the right atrium. 20 In cases of AF recurrence but not of AT after CFAE-guided EEPVI, CFAE in the right atrium might be targeted in the second procedure. Third, this study was not designed as a randomized controlled trial and the statistical analysis might have been influenced by the relatively small size of the subject group.…”
Section: Study Limitationsmentioning
confidence: 99%